Fatherhood and cancer: a commentary on the literature. Issue 2 (16th January 2013) - O'Neill, C.; McCaughan, E.; Semple, C.; Ryan, A.
Fatherhood and cancera commentary on the literature: When a parent is diagnosed with cancer it may create a multitude of concerns and worries, which can be enormously challenging. Despite the increase in research pertaining to parental cancer, there is a paucity of knowledge addressing the impact of cancer on fathers. Fathers' roles are evolving, becoming increasingly diverse and multidimensional. This paper aims to uncover some issues that may be relevant for fathers with cancer. A cancer diagnosis may not solely impact on a man's identity but also on the lives of his children given the contemporary shift from patriarch to more diverse roles. Men and women may share commonalities when diagnosed with cancer but they also experience differences emphasising the need for gender‐sensitive care. This paper highlights the significant role and function that fathers have in their children's lives. It is important that healthcare professionals are aware and pay attention to how gendered responses shape fathers' masculinity and consequently the cancer experience and parenting role. Furthermore this paper highlights the need to gather additional evidence on fathers' experiences when diagnosed and living with cancer. This knowledge can then be used to inform healthcare policy to target fathers, which will benefit both fathers and their children.